2023
DOI: 10.3390/ijms24129850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influence on Treatment Response in Psoriasis: New Insights into Personalized Medicine

Emilio Berna-Rico,
Javier Perez-Bootello,
Carlota Abbad-Jaime de Aragon
et al.

Abstract: Psoriasis is a chronic inflammatory disease with an established genetic background. The HLA-Cw*06 allele and different polymorphisms in genes involved in inflammatory responses and keratinocyte proliferation have been associated with the development of the disease. Despite the effectiveness and safety of psoriasis treatment, a significant percentage of patients still do not achieve adequate disease control. Pharmacogenetic and pharmacogenomic studies on how genetic variations affect drug efficacy and toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 156 publications
0
5
0
1
Order By: Relevance
“…In order to evaluate the identified associations (listed in Table 2 , Table 3 and Table 4 ) and their potential clinical application, we explored the literature for previous associations with autoimmune diseases or diseases with an autoimmune component. Indeed, previous studies have shown that SNPs associated with the response to Ps treatment are also associated with Ps susceptibility [ 27 , 28 ]. Specifically, rs892085 and rs322151, located downstream of PDE4A , have been associated with Ps and PsA [ 29 , 30 , 31 ] and systemic sclerosis, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the identified associations (listed in Table 2 , Table 3 and Table 4 ) and their potential clinical application, we explored the literature for previous associations with autoimmune diseases or diseases with an autoimmune component. Indeed, previous studies have shown that SNPs associated with the response to Ps treatment are also associated with Ps susceptibility [ 27 , 28 ]. Specifically, rs892085 and rs322151, located downstream of PDE4A , have been associated with Ps and PsA [ 29 , 30 , 31 ] and systemic sclerosis, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With response to biologic drugs typically being heterogenous, one hypothesis is that this response reflects genetic variance between patients or genetically distinct disease subsets with distinct pathogeneses. The effect of genetics on anti-TNF response is well characterized, with TNF-α, TNFRSF1A, TNFRSF1B, TNFAIP3, FCGR2A, FCGR3A, IL-17F, IL-17R, and IL-23R suggested to modulate response [126], however, few studies explore the interaction of IL-17 and IL-23 inhibitors with genetics. Ustekinumab shows a higher efficacy and faster response time in HLA-Cw*06 positive patients than in negative patients [126], and Van den Reek et al found that the IL12B rs3213094-T allele increased efficacy and TNFAIP3 rs610604-G allele predicting a worse outcome [127], however other studies were unable to replicate this.…”
Section: Biologic Efficacy In Psoriasismentioning
confidence: 99%
“…The effect of genetics on anti-TNF response is well characterized, with TNF-α, TNFRSF1A, TNFRSF1B, TNFAIP3, FCGR2A, FCGR3A, IL-17F, IL-17R, and IL-23R suggested to modulate response [126], however, few studies explore the interaction of IL-17 and IL-23 inhibitors with genetics. Ustekinumab shows a higher efficacy and faster response time in HLA-Cw*06 positive patients than in negative patients [126], and Van den Reek et al found that the IL12B rs3213094-T allele increased efficacy and TNFAIP3 rs610604-G allele predicting a worse outcome [127], however other studies were unable to replicate this. The SUPREME study found that HLA-Cw*06 status did not influence response to secuk-inumab [128], however the two Italian studies predicted a higher PASI90 in HLA-Cw*06 positive patients [129,130].…”
Section: Biologic Efficacy In Psoriasismentioning
confidence: 99%
“…Research focused on pharmacogenetics, pharmacogenomics, and the impact of genetic variations on drug efficacy and adverse reactions could provide valuable insights in this context. Although studies are variable, it appears that genetic variations in the Vitamin D Receptor (VDR) gene might have a link to treatment response involving calcipotriol or other vitamin D analogs among people with psoriasis [9]. Associations between increased minor allele frequency distribution with better apremilast therapy outcomes were found for SNPs located at IL1β, IL4, IL23R, Tumour Necrosis Factor alpha (TNFα) [10].…”
Section: Introductionmentioning
confidence: 99%